Traffic calming in the vicinity of schools - Zeinab Aliyas, 1986-; Muhammad Zaly Shah Muhammad Hussein; Fakulti Alam Bina (2012)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2012